Maternal employment in high-value agriculture and child nutrition: Evidence from the Ethiopian cut-flower industry - Astewale Bimr Melaku; Matin Qaim; Bethelhem Legesse Debela (University of Bonn, Center for Development Research (ZEF), 2023)
In many countries of the Global South, agri-food supply chains are transforming rapidly. One important feature of this transformation is growth in certain high-value agricultural subsectors, such as horticulture and cut-flowers for export. Growth in high-value agriculture often creates new employment opportunities, especially for women. More employment can lead to higher rural incomes, but the broader implications for social welfare are not yet sufficiently understood. Here, we use survey data from Ethiopia to investigate the effects of women's employment in floriculture on child nutrition, focusing on children aged 0-5 years. We develop and estimate endogenous switching regressions to account for possible endogeneity. Our results suggest that maternal employment in floriculture negatively affects child height-for-age and weight-for-age z-scores (HAZ and WAZ). Exploration of the underlying mechanisms reveals that floriculture employment may influence time allocation, dietary quality, income, and female financial autonomy. Maternal employment is negatively associated with time spent on childcare and consumption of animal-sourced foods.
Keywords: C24; J43; N57; Q18; 330; Women employment; Child nutrition; Agri-food value chains; Floriculture; Africa; Ethiopia